Multiple Approaches to Islam (Al-Jamiah Research Centre, 2010)
The publication of the following articles by Al-Jamiâah shows howÂ rich the subjects of Islamic studies are. From contemporary to classical themes there are gaps still left. This further proves that Islam, like any other religion, as a system of belief and cultural production whichÂ serves as a context wherein textual works and norms are produced, can be approached from many dimensions. The texts, including books and other form of records, are always open to all readers, who can offer various approaches. Both classical and contemporary studies of IslamÂ are faced with various challenges which beg more perspectives. Although classical texts seem muted, new understanding is often born, when new approaches with different perspectives are employed. Likewise,Â contemporary issues are of course dynamics. Studies of the current issues should flow dynamically in the way in which Muslim society progresses with an unpredicted pattern. Studies with new perspectives are always welcome.